Morphology of Leaves Cuticle by Fringe Projection - Cordero-Carrasco, R (2011)
The development of this work is important in the morphological study of plant parts, specifically in the study of the cuticle of fruits or leaves. The implemented optical technique for fringe projection can identify potential fracture zones which damage the presentation of the fruits impacting business as well as producing them. Specifically, we obtained information on the thickness of a cuticle corresponding to the abaxial surface of a leaf of apple (Malus domestica) of the variety Golden Delicious. © 2011 SPIE.